Classification of the sperm chromatin compaction alterations in bulls (Bos taurus) and its correlation with the efficiency of the in vitro production of embryos - Sara Hissae Hiraiwa; P. Alves; Bruno Augusto Nassif Travençolo; Muller Carrara Martins; Marcelo Emı́lio Beletti (2021)
This paper proposes to classify the sperm chromatin compaction alterations in bulls, according to the affected area location and its objective is evaluating the correlation of the intensity, the heterogeneity and these kinds of chromatin decompaction with the rates of cleavage and the formation of blastocysts of in vitro production of embryos (IVPE). It was used several subfertile animals sperm samples, which were evaluated using the toluidine blue staining and computer image analysis, making possible the categorization of the chromatin decompaction according to their location. The percentages of chromatin decompaction and heterogeneity were also evaluated. IVPEs were done and the rates of cleavage and of blastocysts were correlated with the chromatin characteristics. It made possible the classification of the chromatin decompaction according to the head affected part in at least four types: base decompaction, basal half decompaction, central axis decompaction, total decompaction. Based on the correlation, it can be implicated that each type of classification has different influences on the bull fertility. It made possible understanding that sperms amount with 5% or more of chromatin decompaction intensity interferes in the bull fertility and this condition can be featured as an uncompensable defect, while the heterogeneity of chromatin is not an important factor in the IVPE results.